Transient deficiency of antithrombin during pregnancy in a woman with a history of reproductive losses - L. O. Buzyan; V. S. Chulkov (Акушерство, гинекология и репродукция)
Antithrombin deficiency is associated with a high risk of thrombotic events and obstetric complications. Even under an antithrombotic therapy, adverse pregnancy outcomes may occur. We present a case of successful pregnancy completion in a woman with newly diagnosed antithrombin deficiency and a history of miscarriages without thrombotic events. In the postpartum period, her antithrombin level restored to normal.